El control legislativo de la burocracia: un estado del arte (2008)
This article carries out a brief analysis on the different academic proposals about the executive-legislative relations in Latin-America, with especial attention to the role that the congress plays as aninstitution in charge of controlling the administration. Furthermore, the author highlights importantcontributions –both theoretical and empirical– on the cases of the United States and Germany, with theobjective of building on the concept of political oversight and to demonstrate that, in some cases, theinfluence of the Congress on the administration is plausible.